Murder of an Amish bridegroom - Johns, Patricia (Romance writer) (Johns, Patricia (Romance writer). Amish seamstress mystery, 2023)
"The quiet Amish lifestyle isn't all that it seems in this debut cozy mystery series, for fans of Amanda Flower and Wanda E. Brunstetter. Petunia Yoder is Blueberry, Pennsylvania's youngest old maid, at twenty-two years of age, and completely unmarriageable. But she's determined to celebrate her friends' weddings with joy and a full heart. Unfortunately, Petunia's best friend, Eden Beiler, is playing a dangerous game with a man who is ruining her reputation. Ike Smoker is the community's iceman--the one who cuts, stores, and sells the ice--and when Petunia discovers him dead with an ice pick in his chest, Eden is found on the scene with blood on her hands. Homicide detective Asher Nate is new to the area, and he has a challenge on his hands. The Amish community sticks close together, and he doesn't understand the subtleties and nuances of the clues he uncovers. He needs an Amish interpreter, and he asks Petunia if she'll help. In a bid to keep her best friend out of prison, she agrees. The community is filled with people who had good reason to hate Ike Smoker, especially as Petunia and Asher begin to uncover his secrets. Was someone trying to protect their family's reputation? Or to exact revenge for a sin buried deep in the past? There's a litany of damning clues that litters the ground--and if Petunia and Asher can't come up with the truth, they could end up as the next ones on the killer's list."--provided by publisher.